THE RELATION BETWEEN DIRECT PRESIDENTIAL ELECTION SYSTEM WITH THE NATIONAL DEVELOPMENT PLAN - Sugara, Abbas Raga (Scholar Center, 2021)
Many criticized RPJP-RPJMN as the national development plan for suffering a setback. From a historical view, a comparison to GBHN is inevitable as the main argument is through the GBHN, the direction and purpose of the government wheel journey will be easier to understand so that it is quite easy to correct the level of success and achievement that is inscribed by a government in power. The problem is whether the direct presidential election system is being implemented today is the reason why GBHN is removed as a national development plan? The study is analyzed through pure legal research. The result is that the amendment to the 1945 Constitution in Article 6A determines that the Presidential election is directly elected by the people has implications for the abolition of GBHN in Article 3 of the 1945 Constitution.